Postnatal development of cerebellar zones revealed by neurofilament heavy chain protein expression - Joshua J White; Roy V Sillitoe; Roy V Sillitoe (Frontiers Media S.A., 2013)
The cerebellum is organized into parasagittal zones that control sensory-motor behavior. Although the architecture of adult zones is well understood, very little is known about how zones emerge during development. Understanding the process of zone formation is an essential step towards unraveling how circuits are constructed to support specific behaviors. Therefore, we focused this study on postnatal development to determine the spatial and temporal changes that establish zonal patterns during circuit formation. We used a combination of wholemount and tissue section immunohistochemistry in mice to show that the cytoskeletal protein neurofilament heavy chain (NFH) is a robust marker for postnatal cerebellar zonal patterning. The patterned expression of NFH is initiated shortly after birth, and compared to the domains of several known zonal markers such as zebrin II, HSP25, neurogranin, and phospholipase Cβ4 (PLCβ4), NFH does not exhibit transient expression patterns that are typically remodeled between stages, and the adult zones do not emerge after a period of uniform expression in all lobules. Instead, we found that throughout postnatal development NFH gradually reveals distinct zones in each cerebellar lobule. The boundaries of individual NFH zones sharpen over time, as zones are refined during the second and third weeks after birth. Double labeling with neurogranin and PLCβ4 further revealed that although the postnatal expression of NFH is spatially and temporally unique, its pattern of zones respects a fundamental and well-known molecular topography in the cerebellum. The dynamics of NFH expression support the hypothesis that adult circuits are derived from an embryonic map that is refined into zones during the first three-weeks of life.